Direct involvement of the TEN domain at the active site of human telomerase - Jurczyluk, Julie (Oxford University Press, 2011)
Telomerase is a ribonucleoprotein that adds DNA to the ends of chromosomes. The catalytic protein subunit of telomerase (TERT) contains an N-terminal domain (TEN) that is important for activity and processivity. Here we describe a mutation in the TEN domain of human TERT that results in a greatly increased primer K(d), supporting a role for the TEN domain in DNA affinity. Measurement of enzyme kinetic parameters has revealed that this mutant enzyme is also defective in dNTP polymerization, particularly while copying position 51 of the RNA template. The catalytic defect is independent of the presence of binding interactions at the 5′-region of the DNA primer, and is not a defect in translocation rate. These data suggest that the TEN domain is involved in conformational changes required to position the 3′-end of the primer in the active site during nucleotide addition, a function which is distinct from the role of the TEN domain in providing DNA binding affinity.